2001
DOI: 10.1097/00008390-200110000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin and tamoxifen sensitize human melanoma cells to hyperthermia

Abstract: Hyperthermia produces regression of human cancer. Because hyperthermia has produced only limited results, attention has focused on searching for substances able to sensitize tumour cells to the effects of hyperthermia. The flavonoid quercetin has been reported to be a hyperthermic sensitizer in ovarian and uterine cervical tumours and in leukaemia. Quercetin and tamoxifen inhibit melanoma cell growth. We therefore investigated whether quercetin and tamoxifen can sensitize M10, M14 and MNT1 human melanoma cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 31 publications
1
24
1
Order By: Relevance
“…However, other studies have proved that hyperthermia can induce or up-regulate mdr-1 gene expression. The mechanism may be contributed to heat shock factor-DNA binding in the promoter region of the mdr-1 gene or activation of p38 [16][17][18][19] . So, further study is necessary to investigate the detailed mechanism why hyperthermia and Nef can inhibit the mdr-1/P-gp expression in these backgrounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other studies have proved that hyperthermia can induce or up-regulate mdr-1 gene expression. The mechanism may be contributed to heat shock factor-DNA binding in the promoter region of the mdr-1 gene or activation of p38 [16][17][18][19] . So, further study is necessary to investigate the detailed mechanism why hyperthermia and Nef can inhibit the mdr-1/P-gp expression in these backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…Some observations found that hyperthermia can decrease P-gp expression [14,15] . Other researches have proved that hyperthermia can induce or up-regulate mdr-1 gene expression [16][17][18][19] . The different results raise some interesting questions: (1) Does hyperthermia exert an influence on mdr-1/P-gp expression in drug-resistant gastric cancer cells?…”
mentioning
confidence: 99%
“…Depending on cell type and treatments applied, heat shock through the induction of Hsps can protect against the deleterious effects induced, for example, by doxorubicin [20], TNFa [21], TRAIL [22] and CD95 (Fas) [23]. However, in other types of cells, hyperthermia enhances apoptosis induced by radiations [24], Gemcitabin [25], Oxaliplatin [26], Quercetin and Tamoxifen [27]. In T-lymphocytes, heat shock was also found to stimulate apoptosis induced by death receptors pathways such as those triggered by CD95 ligand [28] or TRAIL [29].…”
Section: Introductionmentioning
confidence: 99%
“…6,26) Similarly, the ability of quercetin to induce irreversible contact-independent effects on melanoma-cell growth has not been evaluated to date, since quercetin was kept in the culture media until the time of measurement. 6,7,27,28) These issues were addressed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis became significant at concentrations of 200 mm and up, started 24 h after removal of quercetin, and reached a peak after 48 h. In previous studies, apoptosis was measured and detected immediately after ending cell exposure to quercetin, 6,26) but, in those studies, the cells were exposed to quercetin for 24 h. Therefore, it is likely that they detected late rather than immediate-type apoptosis. Similarly, UVB irradiation caused significant increases in apoptosis beginning 24 h after irradiation.…”
Section: Quercetin Causes Late Apoptosismentioning
confidence: 93%